2008
DOI: 10.1021/es7025054
|View full text |Cite
|
Sign up to set email alerts
|

Toward Understanding the Efficacy and Mechanism of Opuntia spp. as a Natural Coagulant for Potential Application in Water Treatment

Abstract: Historically, there is evidence to suggest that communities in the developing world have used plant-based materials as one strategy for purifying drinking water. In this study, the coagulant properties of Opuntia spp., a species of cactus, are quantitatively evaluated for the first time. Opuntia spp. was evaluated for turbidity removal from synthetic water samples, and steps were made toward elucidating the underlying coagulation mechanism. In model turbid water using kaolin clay particles at pH 10, Opuntia sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
141
1
28

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(178 citation statements)
references
References 36 publications
8
141
1
28
Order By: Relevance
“…Mucilage in cactus opuntia has fiber such as l-rhamanosei, l-arabinose, d-galactose, d-xyloose, and galacturonic acid, predominantly during a bridging coagulation method solution particulates carry out indirectly contact from the cactus genus [24]. The most capable coagulation and active element is galacturonic acid, it is wellknown 50% of turbidity removal [25].…”
Section: Plant-based Coagulants (Pbc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Mucilage in cactus opuntia has fiber such as l-rhamanosei, l-arabinose, d-galactose, d-xyloose, and galacturonic acid, predominantly during a bridging coagulation method solution particulates carry out indirectly contact from the cactus genus [24]. The most capable coagulation and active element is galacturonic acid, it is wellknown 50% of turbidity removal [25].…”
Section: Plant-based Coagulants (Pbc)mentioning
confidence: 99%
“…To shrink cyanogenic & phytate substance to maintain their natural value, altered methods are adopted in sinking cyanogenic glycoside like sun-drying, ensiling, and soaking + sun-drying. Peels are chopped to obtain good quality 2 cm for easy compression, and sagging for two days to decrease moisture substance from 70-75% to about 40% [25]. After 21 days cassava peel silage was observe as light brown in appearance, with satisfying odour.…”
Section: Plant-based Coagulants (Pbc)mentioning
confidence: 99%
“…However, these traditional coagulants have several disadvantages, which include: large volume of sludge [7]; dissolution of metals/constituents into after treatment sludge, under performance and corrosiveness at lower pH and pKa (dissociation constant of a solution) [8]. In addition, Miller et al [9] and Crapper et al [10], reported that these alum-based chemical coagulants can cause pre-senile dementia in human.…”
Section: Introductionmentioning
confidence: 99%
“…This coagulant, under optimal conditions, can achieve between 90 % and 99 % efficiency on removing microorganisms [4]. However, it has drawbacks, such as the fact that the residual aluminum resulted from the process of coagulationflocculation has a high eco-toxicological and economic impact when is discarded into the environment through the treated sludge, and the high cost for communities involved in its import and transport [5].…”
Section: Introductionmentioning
confidence: 99%